Production of 11C, 13N and 15O in proton-induced nuclear reactions up to 200 MeV - Rodríguez-González, T.; Guerrero, C.; Bäcker, C.M.; Bauer, J.; Bäumer, C.; Brons, S.; Jentzen, W.; Jiménez-Ramos, M.C.; Millán-Callado, M.Á.; Schömers, C.; Timmermann, B.; Quesada, J.M.; et al. (Nuclear data sheets, 2023)
Production cross sections of light positron emitters 11C (t1/2=20.36 min), 13N (t1/2=9.97 min) and 15O (t1/2=122 s) have been measured for proton-induced reactions on the main relevant constituents of the human body (C, N and O) from threshold up to 200 MeV of proton incident energy. This has been accomplished by means of two complementary experiments at the clinical proton treatment centers WPE (Essen) and HIT (Heidelberg), both in Germany. In the first case, the multi-foil activation technique was combined with PET imaging, a methodology previously developed at CNA (Seville, Spain). In the second experiment, aimed at energies below 50 MeV, the activation of single foils was measured with conventional LaBr3 detectors. In both cases the IAEA monitor reaction natCu(p,x)63Zn data was used for validation purposes. The most complete and accurate set of excitation functions for the production of light-positron emitters 11C, 13N and 15O in proton induced reactions on human tissue up to 200 MeV is presented. These data are needed for nuclear reaction model development and are extremely important to improve the accuracy of the PET range verification in proton radiotherapy. Seven excitation functions have been measured: 12C(p,x)11C, 14N(p,x)11C, 14N(p,x)13N, 14N(p,γ)15O, 16O(p,x)11C, 16O(p,x)13N and 16O(p,x)15O up to 200 MeV of proton incident energy.